In Vivo Confocal Microscopy Shows Alterations in Nerve Density and Dendritiform Cell Density in Fuchs’ Endothelial Corneal Dystrophy - Aggarwal, Shruti (Am J Ophthalmol, 2018)
PURPOSE: To evaluate corneal nerve and immune cell alterations in Fuchs’ endothelial corneal dystrophy (FECD) and pseudophakic bullous keratopathy (PBK) by laser in vivo confocal microscopy (IVCM) as correlated to sensation and endothelial cell loss. DESIGN: Prospective, cross-sectional, controlled study. METHODS: 33 eyes with FECD were compared to 13 eyes with PBK and 17 normal age-matched control eyes at a tertiary referral center. FECD was classified into early (without edema) and late stage (with edema). Corneal IVCM (HRT3/RCM) and esthesiometry (Cochet-Bonnet) were performed. Corneal nerve and immune dendritic cell (DC) alterations were evaluated and correlated to clinical parameters. RESULTS: FECD and PBK eyes showed significantly (p=0.001) diminished total nerve length (11.5±1.3 and 2.9±0.7mm/mm(2)) and number (8.8±1.1 and 2.2±0.4 n/frame), compared to controls (23.3±8.1 and 25.9±1.3). Decreased nerves corresponded to diminished sensation in FECD (4.9±0.2cm; R=0.32; p=0.045), compared to controls (5.9±0.04). Early and late stage FECD showed significantly reduced total nerve length (13.1±1.4 and 9.9±1.2 mm/mm(2), respectively) and number (8.2±2.5 and 6.5±2.1 n/frame), compared to controls (p<0.001). DC density was significantly increased in FECD (57.8±10.4 cells/mm(2)(;) p=0.01), but not in PBK (47.7±11.6; p=0.60) compared to controls (22.5±4.5). A subset of early FECD patients (7/22) demonstrated very high DC density (>100/mm(2)). CONCLUSION: IVCM demonstrates profound diminishment of subbasal corneal nerves in early, late stage FECD, and PBK, correlating to decreased sensation. Increased DC density in early FECD demonstrates potential subclinical inflammation. The data suggest that reduction in subbasal nerves and increased immune activation may play a role in pathophysiology of FECD.